Apologetics Kenya
______________________________________________________________________________________________________ Apologetics Kenya is passionate about how faith engages with life's big questions in Africa. The ministry started in 2017 to engage skeptics and equip believers with a Christian worldview. We do this through clarifying the gospel and defending it in light of the African challenges to the faith. We carry out this mandate through training, lectures, debates, campus outreaches, speaking engagements, and digital resources. HOW TO REACH US: linktr.ee/apologeticskenya #apologetics #christianity #bible
free